Involving domain experts in the construction of specific domain ontology / Syerina Azlin Md Nasir, Nor Laila Md Noor and Wan Fairos Wan Yaacob - Md Nasir, Syerina Azlin; Md Noor, Nor Laila; Wan Yaacob, Wan Fairos (Unit Penerbitan UiTM Kelantan, 2016)
Most works suggested the involvement of domain experts when handling and dealing with specific-domain knowledge. Therefore, the construction of ontology requires active participation from domain experts especially in preserving the authenticity of digital artifacts, or specifically in this study, the batik artifacts. In this study, two main components of ontology mainly structure and content were identified. For each component, an expert has been chosen to evaluate the ontology syntactically and semantically. Both experts were then being interviewed to gain their rich and contextualised insights. The results show that the participation from domain experts in the early stage of the construction leads to the development of ontology, in this case, Malaysian Batik Heritage Ontology (MBHO) with defined classes and properties. This stage is really crucial in ensuring the interpretation of cultural information can be done properly and accordingly. The developed ontology could later be used by others to further enhance Malaysian textile ontology.